Associations between Life-Time Physical Activity Levels, Sedentary Time and Health Outcomes among Older Adults - Yılmaz, Fikriye; Yılmaz, Atakan (Progress in Nutrition, 2020)
Study Objectives: The aim of the study was to evaluate the associations between the participation levels of the elderly in physical activities through their lives, their sedentary time, and health outcomes. Methods: The data of the study were collected in 2017 with a questionnaire, in which 300 older adults were selected by convenience sampling method in Ankara, Turkey. The questionnaire consists of questions for determining the socio-demographic characteristics and health status of older adults, life-time physical activity indicators, and sedentary time. The research was evaluated with descriptive statistics, Chi-square analysis, Independent Samples t-test, and Pearson correlation coefficient. Results: 53.7% of the 300 older adults participating in the study were female and the average age was 67.74±3.67 years. 58.3% of the participants were categorized as physically “active” currently or in two periods of their lives. The average sedentary time of participants was 5.7 hours for one day. According to Chi-square analysis, those who were younger, those with lower household income, those who evaluated their health status as good and who had no chronic diseases were physically more active (p<0.05). Independent samples t-test results demonstrated that the quality of life scores of those who were physically active was higher in comparison to those who were inactive (p<0.05). According to independent samples t-test, the average sedentary time of those who evaluated their health status as good and those with a chronic disease was found to be shorter. It was found that there was a negative moderately significant relationship between sedentary time and quality of life scores among older adults. Conclusion: In this study, it was concluded that life-time physical activity levels and sedentary time of older adults were an important indicator for their health outcomes.